Lithuanian women in Ravensbrück concentration camp - Bartkutė, Roberta (Genocidas ir rezistencija, 2020)
In the Lithuanian historical memory, imprisonment in Nazi concentration camps (the best known to Lithuanians is Stutthof concentration camp) is entrenched as a largely male experience. This led to the fact that not only the experience of women prisoners has faded, but also the memory of other concentration camps. The most important of these, in researching women’s experiences in Nazi captivity, is Ravensbrück concentration camp. The aim of this paper is to analyse the information available in the memorial’s internal database and online archives about Lithuanian women in Ravensbrück, not only on the basis of statistical data but also by presenting at least partially reconstructed biographies. The results of the research showed that most women of Lithuanian and Polish origin (often this origin was difficult to distinguish) related to Lithuania, the majority of whom were imprisoned in Ravensbrück, were young workers, born between 1920 and 1926, voluntarily or forcibly deported to Germany for works, having committed a certain offence. Also, women of Jewish (9), East Slavic (5), German and (2) Latvian (1) origin, born or having Lithuanian citizenship were imprisoned in Ravensbrück. Thus, a large number of women were brought to Ravensbrück not directly from Lithuania or another place of residence, but already while being in Germany. The fate of only a few women whose records of death from alleged exhaustion or murder at the end of the war have survived is known. Many women survived not only Ravensbrück but also other concentration camps and prisons, where the remaining information (prisoner cards) and post-war documents of German authorities about foreigners who came to Germany during the war have already helped to reconstruct the biographies of some women and can be used in the future while conducting research on prisoners from Lithuania and in other concentration camps.
Keywords: German occupation; repressions; concentration camp; women; jews